Acúmulo de matéria seca e macronutrientes por cultivares de sorgo sacarino - Soares, Edimar Rodrigues [UNESP]; Mendes Coutinho, Edson Luiz [UNESP]; Ramos, Sergio Bispo; Silva, Marcio Silveira da [UNESP]; Barbosa, Jose Carlos [UNESP] (Univ Estadual Londrina, 2014)
Nutrient accumulation curves help us understand the nutritional demands of a crop. The aim of this study was to evaluate the growth and accumulation of macronutrients by the sweet sorghum cultivars CVSW80007, CVSW80147, CVSW82028, CVSW82158. The experiment was conducted in a renewal sugarcane ratoon area at Uchoa county, SP, being deployed in January 2012. The plants were collected in 15 days intervals from the 10th after emergence (DAE). The greatest content of dry matter, N, P, Mg and S, was due to by the CVSW82028 cultivar, while the CVSW82158 extract the greatest amount of K and the CVSW80147 of Ca. The stalks represented the highs percentage of dry matter and nutrient content, except nitrogen and phosphorus, in which grains corresponded to the higher percentage of total absorption. The CVSW80007, CVSW82028 and CVSW82158 cultivars showed the following decreasing nutrient extraction N>K>Ca>Mg>P>S and the CVSW80147, K>N>Ca>Mg>P>S. Considering only the stalks harvest, the decreasing nutrient exportation is the same for all cultivars: K>N>Ca>Mg>S>P. Whereas the decreasing nutrient exportation sequence considering stalks and grain harvest is the following for the CVSW80007, CVSW80147 and CVSW82158 cultivars: K>N>Ca>Mg>P>S and K>N>Ca>Mg>P>S for the CVSW82028.
Accumulation of dry matter and macronutrients in sweet sorghum cultivars
Keywords: Biofuel; Sorghum bicolor (L.) Moench; absorption rate